Ketahanan Gubal Jati Hutan Rakyat Diawetkan dengan Senyawa Boron Menggunakan Metode Tekan Lowry terhadap Serangan Rayap Tanah dan Kayu Kering - Pertiwi, Yus Andhini Bhekti; Sulistyo, Joko (Jurnal Ilmu Kehutanan, 2021)
Nowadays, most of teak wood that available on the market was mainly from comunity forest. Those teak woods were commonly harvested in the early age. The young teak wood from community forests possesses lower proportion of heartwood than sapwood. Those condition was generally had an affect on the wood durability. Although the wood durability was estimated to be low, but the teak wood from community forest was intensively used for furniture and house construction. Therefore, study on the sapwood durability of young teak wood from community forest is necessary. In the present study, the durability of sapwood treated by boron compound (boric acid and borax) as wood preservatives was investigated. The boron concentrations were 5, 7 and 10%. The vacuum process were used to impreg the preservative into the wood specimens called as Lowry method. The efectivity of preservation method were investigated, namely absorption, retention, penetration, efficacy of subterranean and dry-wood termites. The absorption, retention, and penetration of boron compound were 69.10–96.41 kg/m3, 4.53–5.31 kg/m3, and 3.04–3.16 mm, respectively. Absorption, retention, and penetration of preservatives showed an increasing value by increasing the preservatives concentrations, with the highest values were obtained for 10% boron concentration. Graveyard test was used to evaluate the efficacy of boron in teak sapwood to subterranean termites. During 2 months observation, mass loss and degree of wood damage were 0.42-1.37% and 6.31-18.72%. Furthermore, the efficacy of boron was also conducted for dry-wood termites. The mass loss, degree of wood damage, and dry-wood termites mortality after 28 days observation were 1.46-1.67%, 29.45-32.38%, and 87.33-95.33%, respectively. The durability of boron treatened teak sapwood against subterranean and dry-wood termites was increased. The increasing of teak sapwood durability was characterized by reduction of mass loss and degree of wood damage compared to untreated teak sapwood (control).